واقع الحوكمة في البنوك الإسلامية-(دراسة حالة مجموعة البركة المصرفية) خلال عام 2016 - مرغاد, لخضر; جعفر, صليحة (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 05 (2018): مجلة الاقتصاديات المالية البنكية و إدارة الأعمال, 2018)
الملخص هدفت الدراسة إلى معرفة واقع تطبيق معايير الحوكمة في البنوك الإسلامية. وبصفة أساسية  معرفة واقع تطبيق معايير الحوكمة في مجموعة البركة المصرفية خلال عام 2016. وقد توصلت الدراسة إلى أن حوكمة البنوك الإسلامية مختلفة، لأن في البنوك الإسلامية عنصر إضافي لضمان التزامه بأحكام الشريعة الإسلامية. لهذا الغرض توظف البنوك الإسلامية مراقب شرعي أو هيئة الرقابة الشرعية. كما توصلت الدراسة إلى حرص مجموعة البركة المصرفية على وضع إطار عام وفعال وشامل للحوكمة، وعلى ضمان الامتثال في جميع الأوقات لجميع  المعايير و الأنظمة المتعلقة بالممارسات الدولية السليمة للحوكمة( معايير لجنة بازل ومعايير مجلس الخدمات المالية الإسلامية). الكلمات المفتاحية : الحوكمة، حوكمة البنوك الإسلامية، مجموعة البركة المصرفية. Abstract  : This study aims to find out the application  reality of corporate  Governance standards in Islamic banks . In particular  to find out the application reality of Governance standards in the Al Baraka Banking Group(ABG) in2016. The study demonstrated that corporate governance is different for Islamic banks, because the Islamic bank is subject to an additional layer of governance since the suitability of its investment and financing must be in strict conformity with Islamic law . For this purpose, Islamic banks employ an individual sharia Advisor and/or Board. The study also demonstrated that keenness of the the (ABG) ensuring that an adequate, effective, comprehensive and transparent corporate governance framework is in   place,   ensuring compliance at all times with all regulations  concerning  Sound corporate governance  practices (Basel Committee corporate governance Principles and  Islamic Financial Services Board )   .    Keywords: corporate  Governance,  corporate  Governance in Islamic banks, ABG